INTERNATIONAL COLLABORATIVE ONLINE EDUCATION PROGRAM: GEOSPATIAL TECHNOLOGY APPLIED TO DISASTER MANAGEMENT - Ferreira, Hilcéa Santos; de Oliveira, Cleber Silva; Lucaccioni, Claudia Marcela; Mustaro, Pollyana Notargiacomo (Revista Brasileira de Cartografia, 2017)
Disaster Risk Management (DRM) continues to gain political, economic, and geopolitical importance as disasters have caused increasing human and economic losses. Geospatial professionals are attentive of the role of space-derived information in the full cycle of Disaster Management (prevention, preparedness and response), from beyond the immediate response phase to long-term recovery and even to preparedness by informing actions before disasters occur. It is crucial to develop and strengthen relationships with stakeholders and end-users, especially by developing capacity building activities for disaster managers and practitioners. The objective of this paper is to describe the process of establishing an international collaborative capacity development program, with experts from space agencies all around the world, in the Disaster Management area, from its conception to implementation. The strategy for designing the education program is discussed, taking into account ï¬ nancial and human resources and time constraints. The needs assessment and the instructional analysis including learning objectives, outcomes and audience have been performed. This study also includes the challenges of implementing the chosen instructional solution, lessons learned and practical suggestions for using synchronous technologies for instruction when implementing an international online education program in many diï¬€ erent countries. The course was held from April 6t to May 31st, 2015, structured in eight webinars (online seminars) sessions. The demand for the online course (144 registrants from 38 countries in the world), diversity of aï¬ƒ liations and backgrounds conï¬ rms that this subject raises a lot of interest among professionals in need for quality education in this area.